A model system to analyse the ability of human keratinocytes to form hair follicles. Issue 6 (June 2014) - Thangapazham, Rajesh L.; Klover, Peter; Li, Shaowei; Wang, Ji‐an; Sperling, Leonard; Darling, Thomas N.
Abstract Earlier studies showed that dermal cells lose trichogenic capacity with passage, but studies on the effect of keratinocyte passage on human hair follicle neogenesis and graft quality have been hampered by the lack of a suitable model system. We recently documented human hair follicle neogenesis in grafted dermal‐epidermal composites, and in the present study, we determined the effects of keratinocyte passage on hair follicle neogenesis. Dermal equivalents were made with cultured human dermal papilla cells and were overlaid with either primary or passaged human keratinocytes to form dermal‐epidermal composites; these were then grafted onto immunodeficient mice. Superior hair follicle neogenesis was observed using early keratinocyte cultures. Characteristics such as formation of hair shafts and sebaceous glands, presence of hair follicles with features of anagen or telogen follicles, and reproducible hair and skin function parameters make this model a tool to study human hair follicle neogenesis and development.